Power Play of Commensal Bacteria in the Buccal Cavity of Female Nile Tilapia - Abdelhafiz, Yousri; Fernandes, Jorge M. O.; Stefani, Erika; Albanese, Davide; Donati, Claudio; Kiron, Viswanath (Frontiers in Microbiology, 2021)
Fish are widely exposed to higher microbial loads compared to land and air animals. It is known that the microbiome plays an essential role in the health and development of the host. The oral microbiome is vital in females of maternal mouthbrooding species such as Nile tilapia (Oreochromis niloticus). The present study reports for the first time the microbial composition in the buccal cavity of female and male Nile tilapia reared in a recirculating aquaculture system. Mucus samples were collected from the buccal cavity of 58 adult fish ( 1 kg), and 16S rRNA gene amplicon sequencing was used to profile the microbial communities in females and males. The analysis revealed that opportunistic pathogens such as Streptococcus sp. were less abundant in the female buccal cavity. The power play of certain bacteria such as Acinetobacter, Acidobacteria (GP4, GP6) and Saccharibacteria that have known metabolic advantages was evident in females compared to males. Association networks inferred from relative abundances showed few microbe-microbe interactions of opportunistic pathogens in female fish. The findings of opportunistic bacteria and their interactions with other microbes will be valuable for improving Nile tilapia rearing practices. The presence of bacteria with specific functions in the buccal cavity of female fish points to their ability to create a protective microbial ecosystem for the offspring.